Impact of Taxation on the Performance of Small and Medium Size Enterprises (SMEs) in Naalya Kira Municipality, Wasikso District. - Emmanuel Ivu Dramani Bisso (Uganda Christian University, 2023)
This research study investigates the impact of taxes on the financial performance of small scale businesses in Naaliya market-Kira municipality wakiso district Uganda. The study is motivated by the increasing tax burden on SMEs in Uganda, which has led to the winding up of some small scale business enterprises. The study employs a mixed-methods approach, including interviews, surveys, and observation, to collect data from SMEs in Naaliya market. The findings reveal that SMEs in Uganda face multiple taxes, including income tax, value-added tax, and local taxes, which significantly affect their financial performance. The study identifies tax policy, level of technology, government policy, tax ignorance, and level of infrastructure as the key independent variables that affect the performance of SMEs. The study recommends that the government should simplify the tax system, reduce tax rates, and provide tax incentives to SMEs to promote their growth and development. The study concludes that reducing the tax burden on SMEs is crucial for promoting economic growth, creating jobs, and reducing poverty in Uganda. This research study provides valuable insights into the challenges faced by SMEs in Uganda and offers practical recommendations to improve their financial performance.
This is a dissertation.